Conditional Cash Transfers, Adult Work Incentives, and Poverty - Skoufias, Emmanuel; Di Maro, Vincenzo (2012)
Conditional cash transfer (CCT) programmes aim to alleviate poverty through monetary and in-kind benefits, as well as reduce future incidence of poverty by encouraging investments in education, health and nutrition. The success of CCT programmes at reducing poverty depends on whether, and the extent to which, cash transfers affect adult work incentives. In this paper we examine whether the PROGRESA programme of Mexico affects adult participation in the labour market and overall adult leisure time, and we link these effects to the impact of the programme on poverty. Utilising the experimental design of PROGRESA's evaluation sample, we find that the programme does not have any significant effect on adult labour force participation and leisure time. Our findings on adult work incentives are reinforced further by the result that PROGRESA leads to a substantial reduction in poverty. The poverty reduction effects are stronger for the poverty gap and severity of poverty measures.